(untitled) (Modern education and development, 2025)
This in the article milk The positive effect of probiotics on the health and quality of milk when cows are given them, as well as the results of veterinary and sanitary examination of this milk, are highlighted. Probiotics normalize the intestinal microflora, increase immunity and improve the general condition of the body. As a result of the experiments, it was found that the milk of dairy cows given probiotics has high physicochemical and microbiological quality indicators.